Analisis Semiotika Roland Barthes Peran Ibu dalam Lirik Lagu Bertaut Karya Nadin Amizah - Dinda Arya Ramadhani; Nawiroh Vera; Sinta Dwi Utami (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to examine the representation of the mother's role in the lyrics of the song Bertaut by Nadin Amizah using Roland Barthes' semiotic approach. As a medium of mass communication, music does more than provide entertainment; it also shapes social and cultural meaning. The method employed is a descriptive qualitative analysis across three levels of meaning: denotation, connotation, and myth. The research data consists of the song's lyrics, which are analyzed in depth to reveal the symbolic meanings contained within. The results indicate that the lyrics portray the mother as a figure who is ever-present in various aspects of a child's life. Denotatively, the mother’s presence is seen in situations of difficulty, confusion, and life achievements. Connotatively, the mother is interpreted as a source of affection, emotional strength, and a guide in life. At the level of myth, the mother is depicted as a figure synonymous with sacrifice and the source of life. Consequently, Bertaut functions not only as a musical work but also as a medium that represents societal values and perspectives regarding the role of a mother.